Mengurai Audit Report Lag: Apakah Financial Distress Mengubah Peran Komite Audit, Audit tenure, dan Reputasi Auditor? - Aris Sanulika; Wahyu Nurul Hidayati (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the effects of the audit committee, audit tenure, and auditor reputation on Audit Report Lag, as well as to investigate the moderating role of financial distress in property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study adopts a quantitative approach using secondary data obtained from the companies' annual reports and financial statements. The research sample was selected through a purposive sampling technique, resulting in 58 companies with a total of 290 firm-year observations. Data were analyzed using panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). The findings reveal that audit tenure has a negative effect on Audit Report Lag, whereas financial distress has a positive effect on Audit Report Lag. In contrast, the audit committee and auditor reputation do not have a significant effect on Audit Report Lag. Furthermore, the moderating analysis indicates that financial distress does not moderate the relationships between the audit committee, audit tenure, and auditor reputation and Audit Report Lag. These findings suggest that the experience accumulated through longer audit tenure contributes to greater audit efficiency, thereby reducing the time required to complete the audit process. Conversely, companies experiencing financial distress tend to require a longer audit completion period. Therefore, maintaining financial stability and enhancing the effectiveness of the audit process are essential for ensuring the timely issuance of audited financial statements.